The Impact of Sharia Pawnshop Digitalization (TRING by Pegadaian): The Perspective of Maqashid al-Syari'ah : Case Study at the Sharia Pawnshop in Kamal District, Bangkalan Regency - Jamilatus Saadah; Hammam Hammam; Mohd Huefiros Efizi bin Husain; Farid Ardyansyah (Institut Nurul Islam, 2026)
Digital transformation has become a key strategy in the development of Islamic financial institutions, including Pegadaian Syariah. Digitalization not only aims to improve service efficiency but is also expected to strengthen the implementation of maqashid al-syari'ah values oriented towards the benefit of society. This study aims to analyze the effectiveness of maslahat practices in the digitalization of Pegadaian Syari'ah using a qualitative approach. Data were obtained through interviews and observation of digital services. The results show that digitization improves service efficiency and transaction accessibility, but there are still gaps in digital sharia literacy and understanding of electronic contracts. These findings indicate that digital transformation requires education on sharia values so that digitization is not only oriented towards technological efficiency but also towards the realization of the objectives of maqashid al-syari'ah.